Children with non-central nervous system tumors treated with platinum-based chemotherapy are at risk for hearing loss and cognitive impairments - L’Hotta, Allison J.; Spence, Anne; Varughese, Taniya E.; Felts, Kara; Hayashi, Susan S.; Jones-White, Megan; LaFentres, Emily; Lieu, Judith E. C.; Hayashi, Robert J.; King, Allison A. (Frontiers in Pediatrics, 2024)
Childhood cancer survivors (CCS) with chemotherapy induced sensorineural hearing loss (SNHL) are at risk for neurocognitive impairments. The purpose of this study was to determine the relationship between SNHL and cognitive function among CCS.Inclusion: non-CNS solid tumor diagnosis; history of platinum chemotherapy (cisplatin and/or carboplatin); 8-17 years of age; off anti-cancer treatment for ≥ 6 months; and English speaking. Exclusion: history of intrathecal chemotherapy, cranial radiation, or baseline neurocognitive disorder. Participants completed the NIH Toolbox Cognition Battery at enrollment. T-tests were used to compare participants with normal hearing to those with hearing loss and the total sample with established Toolbox normative data (mean: 50; SD: 10).Fifty-seven individuals enrolled; 52 completed full cognitive testing. Participants were on average 12.2 years of age and 7.0 years since treatment completion. Twenty-one participants (40%) received cisplatin, 27 (52%) carboplatin, and 4 (8%) received both. Fifteen participants (29%) demonstrated SNHL based on the better ear. CCS, regardless of the presence or absence of SNHL, demonstrated significantly lower mean cognitive skills compared to the normative sample in attention, executive function, language-vocabulary and oral reading, processing speed, and fluid, crystallized and total composite scores (all p<0.01). Participants with SNHL had significantly lower crystallized composite (vocabulary, oral reading) than those with normal hearing (41.9 vs. 47.2, p<0.05, Cohen's d= 0.62).Conclusions: CCS at risk for platinum induced hearing loss but without cranial radiation or intrathecal chemotherapy exposure demonstrate impaired cognitive skills and those with SNHL demonstrate lower crystallized composite scores.